A Novel Symmetric Anchor Scoring (SAS) Method for Industrial Location Selection: Application to Electric Vehicle Manufacturing in Tamil Nadu, India - S. Mahalakshmi; V. Sathiya; S. Ramabalan; N. Godwin Raja Ebenezer (International Journal of Industrial and Product Design Engineering, 2026)
This work highlights the city-level detail of decision-making enabled by a new MCDM method Symmetry Anchor Scoring (SAS). Generally conventional methods are good at selecting one best and one worst alternative, but not differentiating among the many strong contenders more likely in practice. Linking MCDM methods to the tradition of decision making, the paper discusses the mathematics and analogical basis of SAS design, provides a visual proof of its ideal point symmetry, and illustrates how alternative scoring compromises SAS optimality. SAS innovatively adopts mathematical symmetry as the basis for atypical reference subset comparators. No traditional concept is borrowed from either optimization or comparison frameworks. SAS offshore wind farms locate and the electric vehicle (EV) manufacturing location selection embedded case comparisons demonstrate its performance. Comparing SAS to a leading MCDM method, this paper concludes by recommending areas for application to other decision-making challenges and potential future research strengths. Comparison with AHP-TOPSIS shows that the top ranking alternatives have fairly high levels of consensus. Additionally, through a thorough sensitivity analysis, it is shown that SAS outperforms AHP-TOPSIS in terms of maintaining preference stability over a range of priority scenarios. The SAS solution provides a simple, intuitive, transparent, and weight-free MCDM method when compared to traditional techniques. This will be attractive to decision-makers in industry who are faced with making complex, ill-defined planning decisions, involving multiple competing objectives, and where priorities are uncertain. It was designed for ease of implementation and requires less computational time compared to conventional methods. Additionally, transparency is facilitated by the symmetric tripartite form, a common preference needed to be present for the selected alternative to be ranked among the TOPSIS flight options being compared.
Keywords: Automotive Industry; Novel MCDM method; Sensitivity analysis; Tamil Nadu; electric vehicle manufacturing; industrial location selection; multi-criteria decision making; symmetric anchor scoring